(untitled) (Fiep Bulletin - online, 2013)
The psychic stress is a theme that is being quite discussed in sporting psychology. The objective of this study was to verify which competition situations cause larger psychic alteration in young volleyball athletes. 124 young athletes of 16,06 ± 0,74 years, of SR3 of the Federação Mineira de Voleibol participated in this research. We used as inclusion criterion a "profile iceberg" pattern presented through the POMS questionnaire. The results indicate that the situations that generate more negative psychic stress are: To enter the game hurt (89,52%), Conflicts with the companions (86,29%), inadequate physical Conditioning (86,29%), to hurt during the game (86,29%), inadequate techniquetactics preparation (83,06%), Excessive Nervousness (81,45%) and inadequate game Conditions (80,65%). The psychological preparation concerns the athlete’s interpretation for the situation in which he is inserted and his consequent action answer in the game